Recent Design and Structure-Activity Relationship Studies on the Modifications of DHFR Inhibitors as Anticancer Agents - Wróbel, Agnieszka; Drozdowska, Danuta (Current Medicinal Chemistry, 2021)
Background: Dihydrofolate reductase (DHFR) has been known for decades as a molecular target for antibacterial, antifungal and anti-malarial treatments. This enzyme is becoming increasingly important in the design of new anticancer drugs, which is confirmed by numerous studies including modelling, synthesis and in vitro biological research. This review aims to present and discuss some remarkable recent advances in the research of new DHFR inhibitors with potential anticancer activity. Methods: The scientific literature of the last decade on the different types of DHFR inhibitors has been searched. The studies on design, synthesis and investigation structure-activity relationships were summarized and divided into several subsections depending on the leading molecule and its structural modification. Various methods of synthesis, potential anticancer activity and possible practical applications as DHFR inhibitors of new chemical compounds were described and discussed. Results: This review presents the current state of knowledge on the modification of known DHFR inhibitors and the structures and searches for about eighty new molecules, designed as potential anticancer drugs. In addition, DHFR inhibitors acting on thymidylate synthase (TS), carbon anhydrase (CA) and even DNA-binding are presented in this paper. Conclusion: Thorough physicochemical characterization and biological investigations highlight the structure-activity relationship of DHFR inhibitors. This will enable even better design and synthesis of active compounds, which would have the expected mechanism of action and the desired activity.
Keywords: trimethoprim